2017
DOI: 10.1177/2325957416686836
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Exercise in the Context of HIV: Factors to Consider when Developing and Implementing Community-Based Exercise Programs for People Living with HIV

Abstract: Recommendations for the development and implementation of an accessible and feasible CBE program may enhance exercise participation among PLWH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 26 publications
0
29
0
1
Order By: Relevance
“…Algumas recomendações recentes para proposição de programas de exercício para essa população propostas por Li et al 24 são reforçadas quando analisados os achados do presente estudo e podem ser levadas em consideração na criação de grupos de exercício para essa população: (1) O exercício deve ser oferecido em um formato de grupo para promover a interação social entre os participantes; (2) O programa deve concentrar-se no exercício, mas pode ser complementado com sessões complementares de autogestão e/ou apoio social para aumentar a autoeficácia em relação à prática de exercícios físicos dessa população; (3) Seria importante o programa ser integrado com outras doenças crônicas ou populações em geral para preservar o diagnóstico dos participantes; (4) Oferecer uma estrutura flexível para acomodar as necessidades específicas, como os compromissos familiares, citados no presente estudo, E (5) O programa deve ser acessível financeiramente para maximizar a acessibilidade dos participantes.…”
Section: Discussionunclassified
“…Algumas recomendações recentes para proposição de programas de exercício para essa população propostas por Li et al 24 são reforçadas quando analisados os achados do presente estudo e podem ser levadas em consideração na criação de grupos de exercício para essa população: (1) O exercício deve ser oferecido em um formato de grupo para promover a interação social entre os participantes; (2) O programa deve concentrar-se no exercício, mas pode ser complementado com sessões complementares de autogestão e/ou apoio social para aumentar a autoeficácia em relação à prática de exercícios físicos dessa população; (3) Seria importante o programa ser integrado com outras doenças crônicas ou populações em geral para preservar o diagnóstico dos participantes; (4) Oferecer uma estrutura flexível para acomodar as necessidades específicas, como os compromissos familiares, citados no presente estudo, E (5) O programa deve ser acessível financeiramente para maximizar a acessibilidade dos participantes.…”
Section: Discussionunclassified
“…Some challenges to delivering the TIME™ program, such as program cost and transportation, have been noted previously by people with stroke [ 22 24 ], HIV [ 25 ], and COPD [ 26 , 27 ], as primary barriers to participation in structured exercise programs. Individuals in these studies recommended making CBEP-HRPs widely available [ 24 , 26 ].…”
Section: Main Textmentioning
confidence: 99%
“…The ability to attend programs in close proximity to one’s home was perceived to minimize travel time and cost of transportation, and offset the negative impact of unreliable public transit, and inclement weather on program attendance [ 24 , 26 ]. Subsidization of program cost was desired [ 26 ] as people with physical disability may be receiving a fixed income [ 25 , 26 ]. Results from the current study further highlight the need for financial support of healthcare and recreation partners to sustain the CBEP-HRP model.…”
Section: Main Textmentioning
confidence: 99%
“…In the context of HIV management, a study conducted in the United Kingdom and Canada demonstrated that community-based exercise programs are safe and can improve the quality of life of people living with HIV [ 134 ]. Benefits of community-based rehabilitation include increased social support, enhanced engagement in social activities, and reduced isolation and stigma associated with HIV [ 134 ].…”
Section: Designing Robot-assisted Neurorehabilitation Strategies For mentioning
confidence: 99%
“…In the context of HIV management, a study conducted in the United Kingdom and Canada demonstrated that community-based exercise programs are safe and can improve the quality of life of people living with HIV [ 134 ]. Benefits of community-based rehabilitation include increased social support, enhanced engagement in social activities, and reduced isolation and stigma associated with HIV [ 134 ]. A recent review of 24 studies showed that performing aerobic and resistive exercise is safe and can lead to improvements in cardio-respiratory fitness, strength, body composition and quality of life for adults with HIV [ 96 ].…”
Section: Designing Robot-assisted Neurorehabilitation Strategies For mentioning
confidence: 99%